Optimal Positive Control Assays for Methylation-Specific PCR - Kyle Catalan; Amali Ariyavidana; Yi Jin Liew; Gavin Volpato; Warwick J Locke; Andrew D Johnston; Jason P Ross (Clinical Chemistry, 2026)
Abstract Background Methylation-specific PCR (MSP) is widely used in cancer diagnostics and requires positive controls to confirm DNA integrity and bisulfite conversion. Positive control assays include conversion-specific PCR (CSP) and cytosine-free fragment (CFF) assays. Despite their ubiquity and critical need in MSP assays, positive control assays lack systematic technical performance evaluation. Methods Twelve positive control assays (9 CSP, 3 CFF), including 10 established and 2 novel designs, were evaluated under PCR conditions optimized for modern multiplexed MSP. Assays were tested via DNA-intercalating dye detection across bisulfite-converted and unconverted human DNA templates for amplification consistency across replicates, conversion specificity, primer dimer formation, and PCR efficiency. The 2 novel assays were multiplexed and assessed on cell-free DNA and tissue samples via droplet digital PCR. Results Performance varied markedly across assays. Four CSP assays (ACTB-C, ACTB-D, ACTB-P3, and ZGPAT) demonstrated low replicate variability (SD 0.1–0.6 Cq), near-ideal PCR efficiencies (98%–102%) with strong linearity (R2 ≥ 0.996), minimal amplification of unconverted blood DNA (≤25%), and limited primer dimer formation. Among CFF assays, cfUQ11-CFF showed the best performance, with efficiencies of 92%–97%, strong linearity (R2 ≥ 0.995), and low rates of primer dimer formation (25% of no-template control wells). In multiplex digital PCR on cfDNA, the 2 novel assays demonstrated strong concordance with Qubit-derived DNA estimates (R2 = 0.928 and 0.912). Conclusions Positive control assay selection critically impacts MSP reliability and quantitation. From 12 assays tested, we highlight 4 CSP assays and one CFF assay that meet performance requirements and are suitable for further application.